Innovative activity of enterprises as a system-forming component of the mechanism of sustainable innovation development of the national economy - Vorona , Anna (Social Development and Security, 2020)
The article considers some components of the innovation mechanism of the national economy, their functions and main tasks. The role of enterprises as a system-forming component of sustainable innovative development of the national economy is studied. The level of interest of enterprises in conducting innovative activities is highlighted, the factors influencing the interest of enterprises in innovating the production process are considered. The sources of financing of innovative activity of enterprises are analyzed, the structure of financing of innovation in the period 2012-2018 is investigated. It is noted that lending to innovation, which in many countries is the financial basis of innovation processes, in Ukraine is hampered, in particular, because of limited long-term resources, high cost of innovative bank lending, lack of indirect support in the form of reduced rates for innovation-interested enterprises. Venture investment, franchising, industrial and technology parks in Ukraine are at the stage of initial development. The process of technology transfer as the main indicator of the efficiency of the scientific and technical sphere of economic activity, the legislative component of its existence and the methodology of state support are considered. The dynamics of technology transfer in the period 2012-2018 is analyzed, the conclusion is made on the intensification of innovation in the fields of energy, nanomaterials and technologies, environmental protection, information and communication technologies, as well as reducing the level of innovation in transport, medicine and agriculture.